Surdos e o direito à atenção básica de saúde: desafios e possibilidades - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
The deaf population represents a minority of the Brazilian population that faces many barriers to accessibility when it comes to health care. There are many failures of communication and correct interpretation by health professionals that increase the chances of misdiagnoses, errors in medical records, embarrassment, non-adherence to treatment, suffering and dissatisfaction of the user. This study aimed to verify the difficulties encountered by Deaf people during health care and to analyze the strategies developed and the tools used in the assistance. Method: This is a qualitative, descriptive research, with integrated content analysis. For the argumentation, we analyzed the answers and results of the studies in the articles that were searched in the Scielo, Google Academic and Virtual Health library. And as the results found, among the health professionals, many said they had already seen a patient with deafness and that both, the professional and the Deaf felt some discomfort and also some insecurity in the service and some mentioned that they had already stopped going to the doctor for fear of not being understood or reported some problem, such as pain, discomfort or anguish. And that the participation of companions, even without the mastery of Libras, is the most used strategy, but not the best, as we will see in this study.
Keywords: Surdo; Saúde; Assistência; CNPQ:: CIÊNCIAS DA SAÚDE